1983
DOI: 10.3109/17453678308996576
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Nerve Lesion in the Carpal Tunnel

Abstract: In 16 patients, where the diagnosis carpal tunnel syndrome was electrophysiologically confirmed, the pressure between the median nerve and the carpal ligament was measured peroperatively. At rest the pressure was 18-64 mmHg, mean 31 mmHg. Passive volar and dorsal wrist flexion increased the pressure about three times. Isometric or isotonic maximal contractions of wrist and finger muscles, elicited by tetanic nerve stimulation increased the pressure to three to six times the resting value. These high pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
6

Year Published

1985
1985
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(52 citation statements)
references
References 11 publications
1
45
0
6
Order By: Relevance
“…A localized pressure greater than 50 mm Hg ( =:: 6666 Pa) in the carpal tunnel or a tourniquet with a pressure higher than systolic around the upper arm will cause a conduction block in the median nerve at the wrist (44). Extreme flexingor extension of the wrist causes an increase in pressure in the carpal tunnel that can affect the blood perfusion of the median nerve (49,50). The histopathology of CTS shows coherence with the epidemiologic evidence for physical work load as 344 a risk factor .…”
Section: Experimental and Laboratory Supportmentioning
confidence: 75%
“…A localized pressure greater than 50 mm Hg ( =:: 6666 Pa) in the carpal tunnel or a tourniquet with a pressure higher than systolic around the upper arm will cause a conduction block in the median nerve at the wrist (44). Extreme flexingor extension of the wrist causes an increase in pressure in the carpal tunnel that can affect the blood perfusion of the median nerve (49,50). The histopathology of CTS shows coherence with the epidemiologic evidence for physical work load as 344 a risk factor .…”
Section: Experimental and Laboratory Supportmentioning
confidence: 75%
“…In normal subjects Gelberman et al (1981) observed a pressure of 30 mm Hg in this position. In patients with the carpal tunnel syndrome, a pressure of about 90 mm Hg was observed by both Gelberman et al (1981) and Werner et al (1983). Contractions of the wrist and finger flexor muscles increase the pressure in the carpal tunnel to about 150 mm Hg in patients with a carpal tunnel syndrome (Werner et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…To keep the recording system patent the catheter was continuously perfused with heparinized saline (50 WUmin). This pressure recording system is a routine set-up for pressure determinations in experimental situations and has previously been used when investigating the pressure in the carpal tunnel (Werner et al 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Lundborg et al (73) showed that intracarpal canal pressure can lead to impaired conduction and sensory function of the median nerve in less than 1 h. An increase in carpal tunnel pressure of three to six times the resting value was found during isometric or isotonic maximal contractions of wrist and finger muscles (74). These changes were related to mechanical pressure and perfusion of the median nerve.…”
Section: Nerve Disordersmentioning
confidence: 98%
“…A localized pressure above 50 mm Hg ("'6.65 kPa) in the carpal tunnel or pressure above the systolic level from a tourniquet around the upper arm causes a conduction block in the median nerve at the wrist (73,78). Extreme flexion or extension of the wrist causes an increase of pressure in the carpal tunnel that can affect the blood perfusion of the median nerve (74,87,88).…”
Section: Nerve Disordersmentioning
confidence: 99%